The impact of global climate change on the Indonesian economy - Oktaviani, Rina; Amaliah, Syarifah; Ringler, Claudia; Rosegrant, Mark W.; Sulser, Timothy B. (International Food Policy Research Institute, 2011)
Global climate change influences the economic performance of all countries, and Indonesia is no exception. Under climate change, Indonesia is predicted to experience temperature increases of approximately 0.8°C by 2030. Moreover, rainfall patterns are predicted to change, with the rainy season ending earlier and the length of the rainy season becoming shorter. Climate change affects all economic sectors, but the agricultural sector is generally the hardest hit in terms of the number of poor affected. We assess climate change impacts for Indonesia using an Indonesian computable general equilibrium (CGE) model that focuses on the agricultural sector. Climate change input data were obtained from the International Food Policy Research Institute's International Model for Policy Analysis of Agricultural Commodities and Trade. Our results show that by 2030, global climate change will have a significant and negative effect on the Indonesian economy as a whole. In these projections, we see important impacts for particular sectors in the CGE model, especially for the agricultural sector (both producers and consumers) and in rural areas and for poorer households. Real gross domestic product (GDP) drops slightly and the consumer price index (CPI) increases by a small amount. Negative GDP growth is chiefly the result of adverse impacts on agriculture and agro-based industries, with the largest impact for soybeans, rice, and paddy (unmilled rice). Decreasing output of paddy and rice will adversely affect the country's food security. Domestic prices for paddy and rice increase significantly, pushing up the CPI. Taking international food price shocks into account would increase negative impacts. We find that addressing constraints to agricultural productivity growth through increased public agricultural research investments will be important to counteract adverse impacts of climate change. Enhanced awareness of both government agencies and farmers will be needed for the rural economy to adapt to the adverse impacts of climate change.